2017
DOI: 10.1038/srep45119
|View full text |Cite
|
Sign up to set email alerts
|

Integrative variants, haplotypes and diplotypes of the CAPN3 and FRMD5 genes and several environmental exposures associate with serum lipid variables

Abstract: To determine whether the integrative variants, haplotypes and diplotypes of the calpain 3 (CAPN3) and the FERM domain containing 5 genes (FRMD5) and several environmental exposures are associated with an implication in lipid homeostasis, which are associated with cardiovascular risk. Genotyping of the CAPN3 rs4344713 and FRMD5 rs524908 was performed by Sanger sequencing in 1,640 subjects (Jing, 819 and Han, 821). Multivariate analyses of covariance models that adjusted by age, gender, body mass index (BMI), bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…TC, total cholesterol; TG, triglyceride; HDL-C, high-density lipoprotein cholesterol; LDL-C, low-density lipoprotein cholesterol; ApoA1, apolipoprotein A1; ApoB, apolipoprotein B; ApoA1/B, the ratio of apolipoprotein A1 to apolipoprotein B; BMI, body mass index; Glu, glucose; SBP, systolic blood pressure; DBP, diastolic blood pressure; WC, waist circumference. Joffe et al, 2013;Guo et al, 2017). Likewise, our investigation also produced a significant relationship between age, alcohol consumption, blood pressure, BMI, cigarette smoking, gender, and serum lipid profile in both the Han and Maonan groups, further lending credence to the gene-environment relationship involvement in clinical lipid parameters.…”
Section: A-c-a-a-a-a and A-c-a-supporting
confidence: 68%
“…TC, total cholesterol; TG, triglyceride; HDL-C, high-density lipoprotein cholesterol; LDL-C, low-density lipoprotein cholesterol; ApoA1, apolipoprotein A1; ApoB, apolipoprotein B; ApoA1/B, the ratio of apolipoprotein A1 to apolipoprotein B; BMI, body mass index; Glu, glucose; SBP, systolic blood pressure; DBP, diastolic blood pressure; WC, waist circumference. Joffe et al, 2013;Guo et al, 2017). Likewise, our investigation also produced a significant relationship between age, alcohol consumption, blood pressure, BMI, cigarette smoking, gender, and serum lipid profile in both the Han and Maonan groups, further lending credence to the gene-environment relationship involvement in clinical lipid parameters.…”
Section: A-c-a-a-a-a and A-c-a-supporting
confidence: 68%
“…Guo et al . reported that the FRMD5 gene was associated with lipid homeostasis [ 43 ]. It has been demonstrated that iNOS overexpression or NO donors increased cell death receptor expression and upregulated the p53 pathway [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Study participants were clustered into two distinct groups that differed markedly in clinical characteristics, cardiac structure/function, and indices of cardiac mechanics. Guo et al (2017) used K-means clustering of phenotypic data (clinical and blood pressure characteristics) and found four groups of interest. However, neither of these studies utilized genetic data, which could have provided an additional important dimension to the clustering of hypertension, particularly when combined with phenotypic data.…”
Section: Introductionmentioning
confidence: 99%